2021
DOI: 10.1111/nyas.14571
|View full text |Cite
|
Sign up to set email alerts
|

Associations between private vaccine and antimicrobial consumption across Indian states, 2009–2017

Abstract: Vaccines can reduce antibiotic use and, consequently, antimicrobial resistance by averting vaccine-preventable and secondary infections. We estimated the associations between private vaccine and antibiotic consumption across Indian states during 2009-2017 using monthly and annual consumption data from IQVIA and employed fixedeffects regression and the Arellano-Bond Generalized Method of Moments (GMM) model for panel data regression, which controlled for income and public sector vaccine use indicators obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…However, recent analysis of a trial for an experimental respiratory syncytial virus vaccine showed promising results in reducing antibiotic usage [98,99]. Maternal vaccination could prevent around 3.6 antimicrobial prescription courses per 100 infants in HICs and 5.1 courses per 100 infants in LMICs [100][101][102]. This underlines the connection between vaccination and reduced antibiotic usage.…”
Section: Vaccination Drivesmentioning
confidence: 99%
“…However, recent analysis of a trial for an experimental respiratory syncytial virus vaccine showed promising results in reducing antibiotic usage [98,99]. Maternal vaccination could prevent around 3.6 antimicrobial prescription courses per 100 infants in HICs and 5.1 courses per 100 infants in LMICs [100][101][102]. This underlines the connection between vaccination and reduced antibiotic usage.…”
Section: Vaccination Drivesmentioning
confidence: 99%
“…Panel regression techniques have been used, for example, to assess the relationship between vaccination and AMU in Indian states [ 39 ], the relationship between medical staffing and resistance prevalence in Chinese provinces [ 40 , 41 ], the relationship between lab capacity and AMR in European countries [ 42 ]; and the association between animal AMR and AMU, and animal AMR and human AMR, in European countries [ 43 ].…”
Section: Alternative Ways Of Assessing This Relationshipmentioning
confidence: 99%
“…Vaccines are a powerful tool against the emergence and spread of antimicrobial resistance (AMR). By reducing both drug-resistant and sensitive infections 14 , 20 22 , vaccines reduce reliance on drug therapies and selective pressure driving resistance, averting significant health and economic burden 14 . The World Health Organization has recognized the role of vaccines in combatting AMR and has developed a strategy to optimize the use of vaccines for this purpose 14 , 20 , 21 , 23 – 26 .…”
Section: Introductionmentioning
confidence: 99%